ANALISIS KUALITAS TERJEMAHAN UJARAN RESPON TERHADAP TINDAK TUTUR BERTANYA DALAM NOVEL "ME BEFORE YOU" KARYA JOJO MOYES - Ahmad Kirom; M.R. Nababan; D. Djatmika (PRASASTI: Journal of Linguistics, 2018)
This research discusses the quality of questioning response utterances found in the novel Me Before You and its translation. This aims to describe (1) the types of questioning response utterances, (2) the translation quality of questioning response utterances based on accuracy and acceptability aspects. This research is classified as a descriptive qualitative research which focuses on a single case. The source data of this research is the novel Me Before You and the Indonesian translation version. The data focus on  questioning response utterances. The data are collected with using document analysis, questionnaire and Focus Group Discussion. Furthermore, the data is analyzed the domain, taxonomic, componential analysis and cultural theme. The results of this research is the types of question response utterances based on Searle’s theory is variation such as assertive, directive, commissive and expressive. Then, the quality of questioning response utterances is accurate and acceptable.